Capturing Prosthetic Socket Fitment: Preliminary Results Using an Ultrasound-based Device - (:unkn) unknown (IEEE, 2017)
The acceptance of advanced prosthetic systems by users requires overcoming unique challenges of fitting prostheses to unique user anatomies to achieve systematic performance across a user base. Variations among individuals introduce complexities in fitting the sockets. Due to the difficulty of measuring socket interface characteristics, there is a lack of quantifiable diagnostic fitment information available. As a result, the process of fitting sockets is currently a labor-intensive, manual approach, and can often result in sockets that are uncomfortable, unstable, or impede full range of motion. Additionally, results can be difficult to reproduce reliably. A diagnostic tool has been developed to quantify the relative movement between the socket and the residual bone during the fitting process. The approach leverages low cost and high precision ultrasound transceivers and intuitive visualization software to provide quantifiable socket fitment data. The goal is to enable a systematic socket-fitting strategy that yields reliable and reproducible results. Human subject testing and results are presented that show movement tracking relative to a cuff with an ultrasound transducer with an RMSD of 0.36 mm.
Keywords: MOTION